2018
DOI: 10.1024/0301-1526/a000726
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones and venous thromboembolism – from contraception to hormone replacement therapy

Abstract: The use of sex hormones such as combined oral contraceptives (COC) or hormone replacement therapy (HRT) increases the risk for venous thromboembolism (VTE) considerably, especially in patients with an increased intrinsic risk for thromboembolic complications. Despite public and media attention and increasing scientific evidence, prescription patterns seem to be hard to change. It is well recognized that the patient's baseline risk is the most relevant factor in the absolute risk for developing VTE. The relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Preoperative sex steroid replacement was not agreed upon, even in symptomatic patients with hypogonadism. Some panelists raised concerns that sex steroid administration carries a prothrombotic risk, which may be even higher in the perioperative period (data not shown) [ 29 ]. There are no data suggesting a better surgical outcome if sex steroids are replaced preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative sex steroid replacement was not agreed upon, even in symptomatic patients with hypogonadism. Some panelists raised concerns that sex steroid administration carries a prothrombotic risk, which may be even higher in the perioperative period (data not shown) [ 29 ]. There are no data suggesting a better surgical outcome if sex steroids are replaced preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Transdermal HRT has the benefit of avoiding first pass liver metabolism and as such the effect on the coagulation cascade is much less. 23 Following the concern raised about the increased risk of VTE identified with HRT in the WHI study at the start of the century, further work was done into whether that effect was consistent across all forms of HRT. A retrospective study of women in France showed that the increased risk was associated with oral HRT and not transdermal HRT (OR, 3.5, 95% CI 1.8–6.8, vs. OR 0.9, 95% CI 0.5–1.6).…”
Section: Introductionmentioning
confidence: 99%
“…18 Across the UK, women and the communities they live within are characterised by a wide range of diverse factors, such as ethnicity, occupation, health status, and level of education, 2,13,[19][20][21] which supports the need for personalised care. In addition to this, certain patient groups, for example, women with either chemically induced or surgical menopause, early menopause, or premature ovarian insufficiency [22][23][24] should receive enhanced menopause management for symptom control.…”
Section: Introductionmentioning
confidence: 99%